A Dynamic Systems Theory of epistemic curiosity. (August 2019) - Subaşı, Ahmet
Abstract: The article offers a unified theory of epistemic curiosity within dynamic systems framework. It focuses on complex motivational dynamics leading to epistemic curiosity preferences, which are complexly determined by a combination of motivational, affective and cognitive sub-systems operating within an epistemic ecology. Each sub-system is delimited and modelled as an interacting dimension of the multidimensional causality of the system. The theory focuses on personal variations rather than population averages and offers a framework for modelling personality-based epistemic curiosity characteristics based on an analysis of epistemic curiosity preferences.